Perception And Usage Pattern Of Blogs For Academic Purpose Among Students Of Delta State University, Abraka, Nigeria - Oseruona Oluwaseyi Asak; Moses Ofome Asak (Genius Journals, 2025)
This study examines the perceptions and usage patterns of blogs for academic purposes among undergraduate students at the Delta State University (DSU). As the internet continues to reshape educational paradigms, understanding how students perceive blogging as a tool for academic engagement is imperative. Utilizing a quantitative survey method, data was collected from a sample of 222 undergraduate students from the Faculty of Social Sciences. The study explored key dimensions, including the frequency of blog usage for academic tasks, the motivations driving students to engage with blogs, and the perceived reliability of blogs as academic resources. Findings reveal a paradox where, although a significant majority of respondents read blogs, their utilization for academic purposes remains limited. Students primarily access blogs for entertainment and information rather than for educational enhancements. The results indicate that many students are unaware of the potential benefits that blogging can offer in terms of improving academic performance and facilitating research. Additionally, the study highlights a lack of integration of blogs into the teaching methodologies employed by faculty, which may contribute to the limited academic use of blogs by students. The study underscores the need for increased awareness and educational strategies to encourage the use of blogs in academic contexts at DSU. Recommendations include the development of structured training for students and faculty regarding the educational applications of blogs and the creation of an environment that fosters the integration of blogging into the curriculum.
Keywords: Perception, Usage Pattern, Blogs, Learning Management Systems, Academic, Nigeria